A deep-red fluorophore based on naphthothiadiazole as emitter with hybridized local and charge transfer and ambipolar transporting properties for electroluminescent devices - Arunlimsawat, Suangsiri; Funchien, Patteera; Chasing, Pongsakorn; Saenubol, Atthapon; Sudyoadsuk, Taweesak; Promarak, Vinich (Beilstein Journal of Organic Chemistry, 2023)
Herein, we report the synthesis and characterization of an efficient ambipolar charge-carrier-transporting deep-red fluorophore (TPECNz) based on a donor–acceptor–donor (D–A–D)-type molecule and its application as a non-doped emitter in an organic light-emitting diode (OLED). The fluorophore TPECNz contains naphtho[2,3-c][1,2,5]thiadiazole (Nz) as a strong acceptor unit symmetrically functionalized with N-(4-(1,2,2-triphenylvinyl)phenyl)carbazole as a donor and aggregation-induced emission (AIE) luminogen. The experimental (solvatochromic and emission in THF/water mixtures studies) and theoretical investigations prove that TPECNz retains cooperative hybridized local and charge transfer (HLCT) and weak AIE features. Thanks to its D–A–D-type structure with a proper twist angle between the D and A units, a strong electron deficiency of the Nz unit, and electron-donating and hole-transporting natures of carbazole, TPECNz exhibits a strong deep red emission (λem = 648 nm) with a high fluorescence quantum yield of 96%, outstanding thermal property (Tg = 236 °C), and ambipolar charge-carrier-transporting property with a decent balance of mobility of electrons (1.50 × 10−5 cm2 V−1 s−1) and holes (4.42 × 10−6 cm2 V−1 s−1). TPECNz is successfully employed as a non-doped emitter in an OLED which displays deep red electroluminescent emission peaked at 659 nm with CIE coordinates of (0.664, 0.335)), an EQEmax of 3.32% and exciton utilization efficiency (EUE) of 47%.
Keywords: ambipolar material; deep red fluorophore; hybridized local and charge transfer; naphthothiadiazole; OLED; organic light-emitting diode